In-process investigation of turning process applied with and without cutting fluid / Somkiat Tangjitsitcharoen - Tangjitsitcharoen, Somkiat (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
The aim of this research is to investigate the cutting conditions applied with and without cutting fluid in order to obtain the proper cutting condition for the plain carbon steel with the coated carbide tool based on the consideration of the surface roughness of the machined part, the life of the cutting tool, and the use of minimum quantity lubrication (MQL). The applications of cutting fluid are wet cutting and mist cutting. The dynamometer is installed on the turret of CNC turning machine to measure the in-process cutting force. The in-process cutting forces obtained are examined and analyzed for the machinability of steel under various cutting conditions. The experimentally obtained results showed that the relation between tool wear and surface roughness, the relation between tool wear and cutting force, and the relation between cutting force and surface roughness are correspondent with the same trend. The phenomena of surface roughness and the tool wear can be well explained by the in-process cutting forces obtained. Referring to the criteria, the proper cutting condition determined is the dry cutting at a cutting speed of250 m/min, a feed rate of O. 15 mm/rev, and a depth of cut of 0.5 mm.